Approximating Characteristics of the Classes L_β,p^ψ of Periodic Functions in the Space L_q - Shkapa, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We obtain the exact-order estimates of the best m-term and orthogonal trigonometric approximations and establish the order of trigonometric widths for the classes L_β,p^ψ in the space L_q for some relations between the parameters p and q.